Cs2InGaX6 (X=Cl, Br, or I): Emergent Inorganic Halide Double Perovskites with enhanced optoelectronic characteristics - Kibbou, M.; Haman, Z.; Bouziani, I.; Khossossi, N.; Benhouria, Y.; Essaoudi, I.; Ainane, A.; Ahuja, R. (Current applied physics, 2021)
During the last decade, Inorganic Halide Double Perovskite materials have attracted widespread interest as a promising eco-friendly and non-toxic alternative to lead based hybrid halide organic–inorganic perovskites materials, with outstanding Stability, Structural and electronic properties. In this study, First-Principles density functional theory (DFT) calculations were performed on the structural, stability, electronic and optical properties of the transition metal-based double perovskites materials Cs2InGaX6 (X = Cl, Br, or I). Our results reveal that all these materials exhibit excellent thermodynamic and structural stability owing to their negative formation energies and Goldsmith's factors. It is also observed that Cs2InGaCl6, Cs2InGaBr6, and Cs2InGaI6 materials exhibit band gaps calculated by different functional (GGA-PBE and TB-mpj) in visible-range between 0.89 and 3.24 eV. Furthermore, the computed optical properties reveal strong absorption in UV, visible, and IR range with high optical conductivity and low reflectivity. These obtained results predict that the three transition metal-based double perovskites materials carries promising application in nano-electronic and optoelectronic device applications and can be considered as photovoltaic absorber materials. Schematic illustration of the halide double perovskite absorption over the whole light spectra. [Display omitted] •Electronic and Optical properties of Cs2InGaX6(X: Cl, Br and I) were investigated.•Structural stability was demonstrated.•Semiconductor behavior with indirect and direct bandgaps was shown.•High optical conductivity and low reflectivity were found.•Strong absorption coefficient over the whole light spectra was revealed.